Electron transfer rate analysis of a site-specifically wired copper oxidase. Issue 9 (19th February 2018) - Schlesinger, Orr; Pasi, Mor; Dandela, Rambabu; Meijler, Michael M.; Alfonta, Lital
Abstract : Electron transfer kinetic parameters of site-specifically wired copper oxidase were investigated. Abstract : Electron transfer kinetic parameters of site-specifically wired copper oxidase were investigated. The enzyme's orientation towards the electrode was controlled by incorporation of propargyl-l -lysine as a site-specific anchoring point. Herein, we demonstrate the importance of immobilization orientation and how it affects electron transfer efficiency and kinetics to each of the enzyme's two active sites.